Magnetic field topology, chemical spot distributions, and photometric variability of the Ap star φ Draconis. Issue 4 (12th January 2022) - Kochukhov, O; Papakonstantinou, N; Neiner, C
ABSTRACT: The primary component of the multiple star φ Dra is one of the brightest magnetic chemically peculiar stars in the northern sky. Here, we report results of a comprehensive study of the rotational photometric variability, binarity, magnetic field geometry, and surface chemical spot structure for this star. We derived a precise photometric rotational period of 1.71650213(21) d based on 1 yr of TESS nearly continuous space observations and discovered modulation of the stellar light curve with the phase of the 127.9-d binary orbit due to the light time travel effect. We revised parameters of the binary orbit and detected spectroscopic contribution of the secondary. A tomographic mapping technique was applied to the average intensity and circular polarization profiles derived from Narval high-resolution spectropolarimetric observations. This analysis yielded a detailed map of the global magnetic field topology together with the surface distributions of Si, Cr, and Fe abundances. Magnetic mapping demonstrates that the surface field structure of φ Dra is dominated by a distorted dipolar component with a peak field strength of 1.4 kG and a large asymmetry between the poles. Chemical maps show an enhancement of Cr, Fe and, to a lesser extent, Si in a series of spots encircling intersections of the magnetic and rotational equators. These chemical spot geometries do not directly correlate with either the local field strength or the field inclination.